Study on bed material characteristics and bed load concentration in Sungai Jemberau at Tasik Chini - Nur Fariza, Mohd Ghazali (2019)
The study conducted at Sungai Jemberau sample site. The purpose of this research was to identify the bed material characteristic and bed load concentration in Sungai Jemberau at Tasik Chini because of human activities and also to analyze the bed load discharge of Sungai Jemberau using selected method and to identify the sediment pattern/bed load pattern due to sedimentation process. In order to determine the bed material characteristic and bed load concentration and soil properties, several test were related soil testing conducted in the Geotechnical Laboratory, UMP. Testing that involved are a particle size distribution, moisture content that were carried out in classify properties of the soil sample. The sediment sample sieving test results was classified using Unified Soil Classification System (USCS). Analysis for particle size distribution were shown the highest particle size distribution were Sample 3 - 4.20mm followed by Sample 2 - 3.75mm, Sample 1 and last sample at were 2.75mm and 1.15mm. The moisture content for rainy day which is for Jemberau 2A and Jemberau 2B 34.41% and 39.12% and followed by Chini 1A and Chini 1B when recorded that date is after flood is 22.99% and 10.99%. Furthermore, the surface erosion also gives contribution to the increase of sediment transport and had become the one of main problem at Sungai Jemberau. The bed load pattern at each point were identified through the sedimentation process. The bed load pattern gave the variation of sediment transport modes at Tasik Chini. The bed load discharge were evaluated using two different methods which is direct sampling and formula predictions. Then, by using formulas which were Schoklitsch and Duboys equation. From the analysis of the results of each of the formula, Duboys can be used to predict bed load transport for Sungai Jemberau.